2021
DOI: 10.1016/j.bioorg.2021.105131
|View full text |Cite
|
Sign up to set email alerts
|

3-Alkenyl-2-oxindoles: Synthesis, antiproliferative and antiviral properties against SARS-CoV-2

Abstract: Graphical abstract Sets of 3-alkenyl-2-oxindoles were synthesized of potential antiproliferative (against PaCa-2 and MCF7cancer cell lines) and promising properties against SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 70 publications
(74 reference statements)
0
32
0
Order By: Relevance
“…The standard MTT bioassay technique was considered for antiproliferation properties determination of the synthesized agents 5a–p [79] . Table 1 displays the IC 50 (concentration capable for 50% growth inhibition of the tested cell line) of the synthesized agents 5a–p and reference standards (5-fluorouracil and sunitinib) which are clinically approved drugs against the considered cancer cell lines (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The standard MTT bioassay technique was considered for antiproliferation properties determination of the synthesized agents 5a–p [79] . Table 1 displays the IC 50 (concentration capable for 50% growth inhibition of the tested cell line) of the synthesized agents 5a–p and reference standards (5-fluorouracil and sunitinib) which are clinically approved drugs against the considered cancer cell lines (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometric analysis is an accessible and rapid technique used intensively in medicinal chemical studies for assigning the cell cycle progress of living cells. The detected fluorescence levels estimate quantitatively the DNA content hence; determine the progress of cell cycle [79] , [84] . Compounds 5c and 5o (the most promising agents synthesized with high potency against HCT116) were selected for flow cytometric analysis studies applying the IC 50 value of each respective agent observed through MTT bio-assay, to identify their impact on the progress of cell cycle and accessibility for induction of apoptosis and/or necrosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Girgis et al. performed chemical modifications of sunitinib, then verified the antiviral properties of the products against SARS-CoV-2; they reported that sunitinib may be effective for the treatment of COVID-19 ( 99 ). Zhang et al.…”
Section: Multikinase Inhibitors (Mkis) For Thyroid Cancer During Covi...mentioning
confidence: 99%